2020
DOI: 10.1167/tvst.9.5.17
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Renal Function and Choroidal Thickness in Type 2 Diabetic Patients Detected by Swept-Source Optical Coherence Tomography

Abstract: Relationship between renal function and choroidal thickness in type 2 diabetic patients detected by swept-source optical coherence tomography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The influence of renal function on ChT was confirmed in a wider population of hypertensive non-diabetic individuals, including patients with renal disease unrelated to high BP, where albuminuria and eGFR were found to be inversely and directly related to ChT, respectively [ 69 ]. Similar results come from a total of 1395 ocular treatment-naïve Chinese patients with type 2 diabetes, where ChT decreased in parallel with renal impairment [ 72 ]. Moreover, in a population of 150 individuals (50 with hypertension, 50 with CKD, and 50 healthy controls), a direct association between eGFR and ChT was reported, with evidence that a thinner choroid was associated with increased serum levels of well-known biochemical markers of oxidative stress, inflammation, and endothelial dysfunction, namely asymmetric dimethylarginine, C-reactive protein, IL-6, and endothelin-1 [ 70 ].…”
Section: Retinal and Glomerular Vasculature: Two Sides Of The Same Coinsupporting
confidence: 59%
“…The influence of renal function on ChT was confirmed in a wider population of hypertensive non-diabetic individuals, including patients with renal disease unrelated to high BP, where albuminuria and eGFR were found to be inversely and directly related to ChT, respectively [ 69 ]. Similar results come from a total of 1395 ocular treatment-naïve Chinese patients with type 2 diabetes, where ChT decreased in parallel with renal impairment [ 72 ]. Moreover, in a population of 150 individuals (50 with hypertension, 50 with CKD, and 50 healthy controls), a direct association between eGFR and ChT was reported, with evidence that a thinner choroid was associated with increased serum levels of well-known biochemical markers of oxidative stress, inflammation, and endothelial dysfunction, namely asymmetric dimethylarginine, C-reactive protein, IL-6, and endothelin-1 [ 70 ].…”
Section: Retinal and Glomerular Vasculature: Two Sides Of The Same Coinsupporting
confidence: 59%
“…We have shown in previous studies using spectral domain OCT and SS-OCT that both retina and choroidal layers presented decreased thickness in early stages of DR (no or mild DR), especially in patients with some degree of kidney damage 15 28. According to Liu et al , conflicting results about CT in diabetic eyes can be explained by different protocol designs, patient profiles, adjustment for confounding factors and different devices 29…”
Section: Discussionmentioning
confidence: 97%
“…15 28 According to Liu et al, conflicting results about CT in diabetic eyes can be explained by different protocol designs, patient profiles, adjustment for confounding factors and different devices. 29 The strength of our study is the use of SS-OCT technology, which enables more precise identification of the choroidal-scleral edge and, consequently, more reliable CT and CC density measurements. The main limitations are its cross-sectional design, relatively small sample and limiting sample factors such as the high prevalence of white women and not age-matched controls.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In our sample we found a signi cant trend of thinning in choroid of T2D patients, also observed in nDKD group. Liu et al (2020) suggested that these con icting results could be explained by different protocol designs, patient pro les, adjustment for confounding factors, and different protocol devices [29].…”
Section: Discussionmentioning
confidence: 99%